Análise em regime permanente da conexão da Usina Eólica Cerro Chato no sistema elétrico brasileiro - (:unkn) unknown (Universidade Federal do Pampa, 2013)
Wind power energy has proved to be the source with more growth in the Brazilian energetic field since 2009 and this growth is justified mainly by the volume of energy acquired in the auctions and the prices each time more competitive, if compared to other primary sources. Due to random and variable nature of the wind, the increase in the participation of this energetic font in the energy matrix can become a problem for the planning and control of the electric energy dispatched by the system operator (ONS – Operador Nacional do Sistema Elétrico Brasileiro). As a result, the system operator has develop the network procedures that define specific requirements through Submodulo 3.6 for the establishment and operation of Wind Farms, one of these requirements is the study in permanent regime of the impact of the generation at the electric system, especially in the behavior of the flow stress, in the levels of tension of the bars and in the electric limits of the transmission lines. Therefore, the objective of this study is to make this analysis using the Cerro Chato Wind Farm as reference. The software ANAREDE, developed by CEPEL, was chosen to perform the simulations which consist in the evaluation of the comportment of the electric system facing the variations of power grid and the levels of generation of the electric power plant, comparing 5 operational states, among these, one without contingency, other three with the lost of transmission lines in the “neighborhood” of the Wind farm and finally with the lost of generation of the Thermal Power Plant Candiota. Based on this study, it is expected to determine the possible risks that can come from the connection of the Cerro Chato Wind Farm in the grid.
Keywords: Electrical engineering; Wind power; Electrical systems; CNPQ::ENGENHARIAS; Engenharia elétrica; Energia eólica; Sistemas elétricos